Ekstrak bunga telang sebagai pengganti ZA pada fermentasi nata de banana peel - Oktavia Nurmawaty Sigiro (AGROINTEK, 2023)
Nata is a source of fermented food that contains high fiber. However, to reduce the use of ZA in food, other natural nitrogen sources are needed so that they are safer in the body. This study aims to determine the potential of telang flower or butterfly pea (Clitoria ternatea) extract as a substitute for ZA in fermented fiber-rich foods such as nata de banana peel. The research method was carried out by experimental methods, namely the observation of yield, fiber content, and thickness of  nata de banana peel without the addition of ZA (X1) and with the addition of ZA (X2) with the addition of a concentration of 25 ml and 50 ml of telang flower.The result showed that the highest nata result in terms of yield, fiber content, and nata thickness were nata samples with 50 ml of telang flower extract with the addition of ZA. The sample with telang flower extract without the addition of ZA was the highest in terms of yield and fiber content was nata with 25 ml of telang flower extract. Based on the thickness, nata with 25 ml of telang flower extract without the addition of ZA had a greater thickness than nata with 50 ml of telang flower extract without the addition of ZA. This shows that the sample with the extract of telang flower without the addition of ZA can form nata de banana peel. Therefore, the extract of telang flower can be used as a substitute for ZA in the fermentation process of nata by Acetobacter xylinum. Based on the fiber content produced, the best nata is nata de banana peel which is formed from samples with 25 ml of telang flower extract without the addition of ZA